Growth performance of African catfish Clarias gariepinus cultured in biofloc system at high stocking density - Petrus Hary Tjahja Soedibya; Taufik Budhi Pramono; Emyliana Listiowati (Jurnal Akuakultur Indonesia)
ABSTRACT